Search for the lightning dragon ebook - West, Tracey (Dragon Masters, 2017)
Will the Dragon Masters find the Lightning Dragon? Or will an evil wizard find him first? Pick a book. Grow a Reader!This series is part of Scholastic's early chapter book line, Branches, aimed at newly independent readers. With easy-to-read text, high-interest content, fast-paced plots, and illustrations on every page, these books will boost reading confidence and stamina. Branches books help readers grow!In book #7, the Dragon Masters have to track down the Lightning Dragon! But first, they need to find his Dragon Master — a boy named Carlos. The Lightning Dragon shoots dangerous sparks of energy! Will Carlos be able to connect with his wild dragon? Or does a darker master have plans for the Lightning Dragon?